Aplikasi Perangkat Ajar Kebudayaan Indonesia Berbasis Multimedia - Yosanny, Agustinna; Prasetio, Yen Lina; Halim, Adriani; S. A., Yunair Octaarianti Octaarianti (Bina Nusantara University, 2012)
The purpose of this research is to design a CAI application as a learning support and media to introduce the valuable cultures of Indonesia. The CAI is objected to children or people using computer. The research applied the Interactive Multimedia System Design & Development (IMSDD) method, which consists of system requirement, design consideration, implementation, and evaluation. The result of this research is a CAI application about Indonesian culture based on multimedia that fulfills the user?s need on CAI application. CAI is expected to grow users? interest about Indonesian culture, improve children?s memory capability, and help create the learning process more interesting and fun.